1978
DOI: 10.1051/rnd:19780530
|View full text |Cite
|
Sign up to set email alerts
|

Circadian responses of teleostean oocytes to gonadotropins and prostaglandins determined by cyclic AMP concentration

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Perhaps this low level of reaction indicates that sea bass ovaries have a temporal variation in reponsiveness to the hormone injection. Both in vivo and in vitro evidence suggest that the responsiveness of teleost gonads to hormone stimulation varied at certain times during the day (DE VLAMING and VODICNIK 1977;Kuo and WATANABE 1978;PETER et al 1982). The present results seem to support this view; however, more tests are needed to further elucidate this matter in sea bass.…”
Section: Discussionsupporting
confidence: 59%
“…Perhaps this low level of reaction indicates that sea bass ovaries have a temporal variation in reponsiveness to the hormone injection. Both in vivo and in vitro evidence suggest that the responsiveness of teleost gonads to hormone stimulation varied at certain times during the day (DE VLAMING and VODICNIK 1977;Kuo and WATANABE 1978;PETER et al 1982). The present results seem to support this view; however, more tests are needed to further elucidate this matter in sea bass.…”
Section: Discussionsupporting
confidence: 59%
“…The last study showed that under some e~virQ~~~~ta1 conditions, there was a synchronization between the temporal changes in ovarian se sitivity to GtH and the daily cycle of Gt levels in the plasma. Moreover, it has been shown that the gonadal response to different preparations of gonadotropin, as estimated by measuring the productive of steroids in Fmdulus gvandis (~acGrc~~r et nl., 1985) and the production of c-AMP in the Mugil cephalus (Kuo and Watanabe, 1978), fluctuated during the day.…”
Section: Discussionmentioning
confidence: 98%
“…There are significant daily changes in the amount of cyclic 3'5'-adenosine monophosphate accumulated by oocytes of Mugil cephalus following treatment in vitro with salmon GtH (sGtH), luteinizing hormone (LH), and prostaglandins (Kuo and Watanabe, 1978). A temporal variation in the responsiveness of gonads of teleosts to GtH is further suggested by the finding that there was stimulation of development of gonads of N. crysoleucas when sGtH was injected 3 h after onset of light, but not at 10 h, on conditions of 15.5 h light daily photoperiod (15.5 L 8.5 D) and 15°C (de Vlaming and Vodicnik, 1977).…”
Section: Introductionmentioning
confidence: 99%